EEG neurofeedback treatments in children with ADHD: an updated meta-analysis of randomized controlled trials - Micoulaud-Franchi, Jean-Arthur; Geoffroy, Pierre Alexis; Fond, Guillaume; Lopez, Régis; Bioulac, Stéphanie; Philip, Pierre (Frontiers in Human Neuroscience, 2014)
Objective We undertook a meta-analysis of published Randomized Controlled Trials (RCT) with semi-active control and sham-NF groups to determine whether EEG-NF significantly improves the overall symptoms, inattention and hyperactivity/impulsivity dimensions for probably unblinded assessment (parent assessment) and probably blinded assessment (teacher assessment) in children with Attention Deficit Hyperactivity Disorder (ADHD). Data Sources A systematic review identified independent studies that were eligible for inclusion in a random effects meta-analysis. Data Extraction Effect sizes for ADHD symptoms were expressed as standardized mean differences (SMD) with 95% confidence intervals. Results Five identified studies met eligibility criteria, 263 patients with ADHD were included, 146 patients were trained with EEG-NF. On parent assessment (probably unblinded assessment), the overall ADHD score (SMD=-0.49 [-0.74, -0.24]), the inattention score (SMD=-0.46 [-0.76, -0.15]) and the hyperactivity/impulsivity score (SMD=-0.34 [-0.59, -0.09]) were significantly improved in patients receiving EEG-NF compared to controls. On teacher assessment (probably blinded assessment), only the inattention score was significantly improved in patients receiving EEG-NF compared to controls (SMD=-0.30 [-0.58, -0.03]). Conclusions This meta-analysis of EEG-NF in children with ADHD highlights improvement in the inattention dimension of ADHD symptoms. Future investigations should pay greater attention to adequately blinded studies and EEG-NF protocols that carefully control the implementation and embedding of training.